Analysis of Factors Influencing Local Taxpayers’ Compliance in Paying Rural and Urban Land and Building Tax (Pbb-P2): A Literature Review - Tri Sari Werdoningsih; Saring Suhendro; Ninuk Dewi Kesumaningrum (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
The realization of Rural and Urban Land and Building Tax (PBB-P2) revenue faces significant challenges with arrears reaching 59.27% to 75% in various regions, indicating structural problems in taxpayer compliance. This research aims to identify and analyze factors affecting PBB-P2 taxpayer compliance and analyze the consistency of empirical findings across various contexts. A library research method was employed by analyzing ten journals from 2020-2025 through descriptive-qualitative content analysis techniques. The research results identify three hierarchical layers: core factors with high consistency (tax awareness, tax knowledge, taxpayer income), institutional factors with moderate consistency (service quality), and contextual factors with high inconsistency (tax sanctions, socialization). The determinant contribution of variables ranges from 22.5%-63.7%. The research concludes the need to prioritize strengthening tax awareness and literacy, taxpayer satisfaction-oriented administrative reform, nuanced approaches in sanction implementation, and exploration of emerging factors such as digitalization and institutional trust to develop comprehensive compliance prediction models.